CD154 is a negative regulator of autoaggressive CD8(+) T cells in type 1 diabetes - McGregor, Catrin M. (National Academy of Sciences, 2004)
TNF/CD80 mice, a CD8(+) T cell-mediated model for type 1 diabetes, transgenically express tumor necrosis factor α (TNF-α) and the costimulatory molecule CD80 in their pancreatic islets. Here we show that these molecules bypass the need for CD40–CD154 costimulatory interactions in activation of CD8(+) T cells, allowing us to determine the role of CD40–CD154 signals in regulation of autoaggressive CD8(+) T cells after their in vivo priming. TNF/CD80 CD154-deficient mice rapidly develop diabetes, whereas CD154-sufficient mice do not. This finding correlates with the decreased numbers of CD4(+)CD25(+) T regulatory (T(R)) cells in the islets and pancreatic lymph nodes, in comparison to disease-protected CD154-sufficient mice. Administration of a CD40 agonistic antibody induces a systemic and tissue-specific increase in T(R) cells. However, this increase fails to delay diabetes development in the absence of CD154. Adoptive transfer studies show that CD8(+) T cells from TNF/CD80 CD154-deficient, but not CD154-sufficient, mice are resistant to regulation in vivo. This study provides evidence that CD40-transduced signals initiate T(R) cell increase in vivo and that CD154-transduced signals sensitize autoaggressive CD8(+) T cells to suppression.